2005
DOI: 10.1073/pnas.0501211102
|View full text |Cite
|
Sign up to set email alerts
|

Burn injury causes mitochondrial dysfunction in skeletal muscle

Abstract: Severe burn trauma is generally followed by a catabolic response that leads to muscle wasting and weakness affecting skeletal musculature. Here, we perform whole-genome expression and in vivo NMR spectroscopy studies to define respectively the full set of burn-induced changes in skeletal muscle gene expression and the role of mitochondria in the altered energy expenditure exhibited by burn patients. Our results show 1,136 genes differentially expressed in a mouse hind limb burn model and identify expression pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
100
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 44 publications
18
100
0
Order By: Relevance
“…These findings point to a possible role of amino acid metabolism in the pathogenesis of mitochondrial disease suggesting that: (i) the urea cycle may be crucial in disease progression, and (ii) steps in the arginine metabolic pathway are promising targets for novel therapeutic approaches. The up-regulation of many genes involved in amino acid and protein metabolism is well documented in skeletal muscle mitochondrial dysfunction after burn injury (23), further validating these findings.…”
Section: 'Metabolic Genes' Including Genes Involved In the Lipid Persupporting
confidence: 73%
“…These findings point to a possible role of amino acid metabolism in the pathogenesis of mitochondrial disease suggesting that: (i) the urea cycle may be crucial in disease progression, and (ii) steps in the arginine metabolic pathway are promising targets for novel therapeutic approaches. The up-regulation of many genes involved in amino acid and protein metabolism is well documented in skeletal muscle mitochondrial dysfunction after burn injury (23), further validating these findings.…”
Section: 'Metabolic Genes' Including Genes Involved In the Lipid Persupporting
confidence: 73%
“…Hypermetabolism and inflammation are two hallmarks of the body's response to burn injury (15,16). Our analysis reveals that significantly enriched pathways in C1 include glycosphingolipid biosynthesis-globoseries (5 genes, p value: 8.19E-5), primary immunodeficiency signaling (10 genes, p value: 0.001), keratan sulfate biosynthesis (5 genes, p value: 0.007), galactose metabolism (5 genes, p value: 0.01), ubiquinone biosynthesis (8 genes, p value: 0.01) , death receptor signaling (7 genes, p value: 0.01), and mitochondrial dysfunction (12 genes, p value: 0.01) (the p values are calculated from the hypergeometric test; see SI Text for the details of pathway analysis).…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial dysfunction and mitochondria related ubiquinone biosynthesis are among the top enriched pathways in both C1 and C2 groups, suggesting that mitochondrial functions are significantly affected by both burn and age. A limited number of previous animal studies have found that mitochondrial genes and function are decreased in skeletal muscle, liver, and cardiac muscle following burn injury (16). Fig.…”
Section: Mitochondrial Function Is Differentially Perturbed In Pediatmentioning
confidence: 99%
“…Cutaneous burn and hind limb unloading have an additive effect on muscle atrophy, characterized by loss of muscle mass and decrease in muscle strength in both fast (PL) and slow (SL) twitch muscles. [2][3][4][5] Body weight, muscle wet weight and protein weight of rats in burn group were decreased significantly compared with sham group. [6] Following a large burn, skeletal muscle plays an differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Growing evidence suggests that the main mechanisms underlying skeletal muscle wasting induced by severe burn include activation of ubiquitin-proteasome pathway, [8][9][10] myonuclear apoptosis, [1] mitochondrial dysfunction, [5,7] autophagy [1] signaling pathways driving muscle inflammation, and protein metabolism. [11] MicroRNAs (miRNAs) belong to a group of noncoding small RNAs with a length of 20-24 ribonucleotides, which play a critical role in post-transcriptional regulation of gene expression.…”
mentioning
confidence: 99%